Comparison of clinical pregnancy rates and miscarriage rates in frozen vs selective fresh embryo transfers: a multicentric retrospective analysis - Parab, Avantika; Shrimali, Kalyani; Gutgutia, Rohit; Malik, Sonia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: IVF initially involved making of embryos and transferring in same cycle. However, with advanced freezing techniques, most of the clinics now have shifted to freeze all strategy claiming better pregnancy rates. Our study aims to compare clinical outcomes in frozen vs. selective fresh transfers. We also compared clinical outcomes in these groups in subgroups of PCOS, Poor reserve, tubal factor, endometriosis and male factor. Methods: Multicentric, retrospective study conducted across 65 centers. The IVF cycles were included for a period of 5 years from 1st January 2019 to 31st December 2023. Sub fertile couples between 23 to 43 years of age undergoing self-cycles in antagonist protocol, undergoing embryo transfer with one or two blastocysts. Patients with severe uterine factor infertility (multiple fibroids, unicornuate uterus, Asherman’s syndrome, and severe adenomyosis), patient who had history of previous three or more IVF failure (recurrent implantation failure), patients with bad obstetric history (three or more pregnancy losses) were excluded. Results: Total number of embryo transfers were 38,789. Frozen transfers were 34,407 and 4382 were fresh embryo transfer. Only those patients which had clinically low risk of OHSS and good endometrial thickness with trilaminar appearance were considered for fresh embryo transfers. Clinical pregnancy rates and miscarriage rates were calculated in both the groups. Further, the clinical pregnancy rates and miscarriage rates were also calculated in subgroups like PCOS group (n=3341), tubal factor (n=1929) endometriosis (n=693), low ovarian reserve (n=863) and male factor infertility (n=31963). Conclusions: Our study showed better pregnancy rates with frozen embryo transfers over fresh embryo transfers, more so in endometriosis and male factor infertility. However, even miscarriage rates are higher in frozen embryo transfer except in endometriosis patients.